Effect of strength and high-intensity training on jumping, sprinting, and intermittent endurance performance in prepubertal soccer players - Ferrete, C.; Requena, B.; Suarez-Arrones, L.; Saez de Villarreal, E. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to examine the effects of a 26-week on-field combined strength and high-intensity training on the physical performance capacity among prepubertal soccer players who were undertaking a competitive phase of training. Twenty-four prepubertal soccer players between the age of 8 and 9 years were randomly assigned to 2 groups: a control (C; n = 13) and an experimental group (S; n = 11). Both groups performed an identical soccer-training program, whereas the S group also performed combined strength and high-intensity training before the soccer-specific training. The 15-m sprint time (seconds), countermovement jump (CMJ) displacement, Yo-Yo intermittent endurance test (Yo-Yo IE), and Sit and Reach flexibility were each measured before (baseline) and after 9 (T2), 18 (T3), and 26 weeks (posttest) of training. There were no significant differences between the groups in any of the variables tested at baseline. After 26 weeks, significant improvements were found in the CMJ (6.72%; effect size [ES] = 0.37), Yo-Yo IE (49.57%, ES = 1.39), and Flexibility (7.26%; ES = 0.37) variables for the S group. Conversely, significant decreases were noted for the CMJ (-10.82%; ES = 0.61) and flexibility (-13.09%; ES = 0.94) variables in the C group. A significant negative correlation was found between 15-m sprint time and CMJ (r = -0.77) and Yo-Yo IE (r = -0.77) in the S group. Specific combined strength and high-intensity training in prepubertal soccer players for 26 weeks produced a positive effect on performance qualities highly specific to soccer. Therefore, we propose modifications to current training methodology for prepubertal soccer players to include strength and high-intensity training for athlete preparation in this sport.